Mexico-U.S. Migration in Time: From Economic to Social Mechanisms. Issue 1 (July 2019) - Asad, Asad L.; Garip, Filiz
This article adopts a mixed-methods approach to illustrate how economic, political, and social mechanisms work across time to shape individuals' migration decisions. First, using large-scale survey data from the Mexican Migration Project, we show that economic, political, and social factors all matter for migration decisions but that social factors come to matter most for migration over time. Second, drawing on 120 in-depth interviews with migrants and their family members in four Mexican communities, we find that communities' migration histories shape how economic, political, and social factors contribute to migration decisions at different points in time. In communities with limited migration histories, individuals migrate to relieve economic pressures on themselves or other household members. In communities with more established migration histories, information and assistance from current or returned migrants help to overcome potential barriers to making the journey. Finally, in communities with a high incidence of migration, social factors act as independent causes of migration—apart from economic needs. These findings provide a deeper understanding of the processes underlying Mexico-U.S. migration, which is crucial for anticipating future flows and crafting policy responses.